Lia Overbrook’s anorexia in Laurie Halse Anderson’s Wintergirls - Erro Ahmad Surya; Danu Wahyono (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study is about Lia Overbrook's Anorexia in Laurie Halse Anderson's Wintergirls. There is one problem statements for this study, that is How is Lia’s anorexia described in Wintergirls? The aims of this study are to analyze Lia’s anorexia. To conduct the study, the researcher uses psychological approach. This study uses descriptive qualitative method because the source of data comes from the utterances in the novel. Lia develops Anorexia Nervosa because of the pressure and societal expectations from her mother. Lia finds her solace in internet. She exposed with dangerous advice that further perpetuate the cycle of disordered eating. Lia experiences extreme weight loss because her obsession in weight loss and fuel her disordered behaviors, that is anorexia nervosa. Lia' preoccupation with food calories, and self-blame of her death friend develop her Anorexia Nervosa.